2018
DOI: 10.15666/aeer/1605_64096417
|View full text |Cite
|
Sign up to set email alerts
|

Study on Allelopathy of Three Species of Pinus in North China

Abstract: Two-year-old seedlings of Pinus species typical in North China (Pinus thunbergii, Pinus tabuliformis and Pinus koraiensis) were selected as the research object. The water extracted from the litter of P. thunbergii, P. tabuliformis and P. koraiensis were used to test the changes of photosynthetic pigment Chl. a, Chl. b and allelochemicals. The results were as follows: aqueous extract of P. thunbergii needle litter had significantly low inhibition on P. thunbergii while strongly inhibited P. tabuliformis and P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Essential oils of Pinus pinea Linn., where limonene (54.1%), α-pinene (7.7%), and β-pinene (3.4%) were prevailing, inhibited seed germination and seedling growth of weeds Sinapis arvensis L., Lolium rigidum Gaud., and Raphanus raphanistrum L., and at the 2 mL/l concentration was more efficient than herbicide 2,4-D isooctyl ester with the same concentration [154]. Furthermore, recently it was shown that water extracts from the needle litter of Pinus thunbergii , Pinus tabuliformis , and Pinus koraiensis , the main afforestation species in northern China, demonstrated autotoxicity of varying intensity level [156].…”
Section: Allelochemicals In Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential oils of Pinus pinea Linn., where limonene (54.1%), α-pinene (7.7%), and β-pinene (3.4%) were prevailing, inhibited seed germination and seedling growth of weeds Sinapis arvensis L., Lolium rigidum Gaud., and Raphanus raphanistrum L., and at the 2 mL/l concentration was more efficient than herbicide 2,4-D isooctyl ester with the same concentration [154]. Furthermore, recently it was shown that water extracts from the needle litter of Pinus thunbergii , Pinus tabuliformis , and Pinus koraiensis , the main afforestation species in northern China, demonstrated autotoxicity of varying intensity level [156].…”
Section: Allelochemicals In Treesmentioning
confidence: 99%
“…Unlike deciduous, in conifers, the mechanisms of action of allelochemicals are poorly understood. In addition to changes in the activity of antioxidant enzymes under the action of DHAP [260], the inhibitory effect of needle extracts of various pine species [148,156] and Taxus baccata [158] on the content of chlorophyll and photosystem II was also shown. The synergistic effect of the conifer allelochemicals is also noteworthy.…”
Section: Allelochemicals In Treesmentioning
confidence: 99%